Electrodiagnostic study in delayed facial palsy after closed head injury. - Puvanendran, K (1977)
The time course of electrical reactions in this condition varied much from that after section of the facial nerve or after Bell's palsy. It was at least a week before denervation could be suspected in the latter conditions by electrodiagnostic methods. In post-traumatic delayed facial palsy we have demonstrated electrical reactions showing denervation at the time of palsy or even a few days before, and this is probably related to its pathogenesis. Denervation occurred in 82% of cases which is about double the incidence in Bell's palsy.